Determinants of Micro Social Media Influencers (Micro SMIs) Existence Attributes in Pekanbaru City Â - Wildah, Sri Wahyuni; Berampu, Lailan Tawila (Pusat P2M Politeknik Negeri Batam, 2024)
Abstract This article aims to analyze determination of existence attributes of Micro Social Media Influencers (Micro SMIs) and find the highest contribution value in existence attributes. This study focused on respondents aged between 18-34 years who were followers of Instagram @mahasiswa_universitasriau (MUR) accounts and used as a reference. There are 5 variables used in existence attributes of Micro SMIs, Such as Content, Expertise, Attractiveness, credibility, and Trustworthiness. The biggest cross loading values for each variable is perception of usefulness, communication skills, empathy, popularity, trusted followers. The lowest cross loading value of each variable is the frequency of posts, experience, background similarity, close to followers, and honest.